2011
DOI: 10.1007/s12665-011-1038-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on capillary rise from shallow groundwater and critical water table depth of a saline-sodic soil in western Songnen plain of China

Abstract: The objective of this study was to develop an empirical equation for estimating the capillary rise in the saline-sodic soil area of Songnen Plain in China based on the Averianov formula. The capillary rise was observed under five controlled groundwater levels by lysimeters. Field experiment results indicated that capillary rise had close relationship with the groundwater table depth, soil moisture of 10-40 cm soil layer and leaf area index. These factors have been taken into account to develop the empirical eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 12 publications
(13 reference statements)
0
23
0
1
Order By: Relevance
“…For the GW with lower salinity, the GW table should not be shallower than 1.5 m [10]. By research of the effect of shallow underground water on the formation process of salinity-sodicity soil in Songnen Plain, results indicate that the shallow ground water level has already exceeded the critical water level (2-3 m) [11,12]. However, when the groundwater table reached 5 m, the soil salinization still continued and aggravated [13,14], which is unexplainable from the viewpoint that soil salinization is solely caused by the rise of underground capillary water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the GW with lower salinity, the GW table should not be shallower than 1.5 m [10]. By research of the effect of shallow underground water on the formation process of salinity-sodicity soil in Songnen Plain, results indicate that the shallow ground water level has already exceeded the critical water level (2-3 m) [11,12]. However, when the groundwater table reached 5 m, the soil salinization still continued and aggravated [13,14], which is unexplainable from the viewpoint that soil salinization is solely caused by the rise of underground capillary water.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the spatial variation of soil salinity is mainly affected by the environmental factors (the topography, hydrological process and climate conditions). However, very little research has been done on the spatial variation of soil salinity-sodicity and their relation with environment factors in Songnen Plain [12,19]. In addition, regular statistical analysis and regression analysis are mainly employed.…”
Section: Introductionmentioning
confidence: 99%
“…This model proved suitable for estimating short-term mean rate of capillary rise, net long-term capillary rise and season soil salinities in different soil layers. Yang et al (2011) investigated the capillary rise under five controlled groundwater levels by lysimeters and they obtained a good agreement of the modelled capillary rise with the observed data. Werner and Lockinton (2004) noticed the influence of salinization on the water table.…”
Section: Introductionmentioning
confidence: 64%
“…The results of the study showed that in a soil with the presence of green cover, CR depended on the amount of moisture in the root zone (10–40 cm), the leaf area index and groundwater depth. There is a negative and weak correlation between CR and soil moisture, whereas there is a positive relationship with the other two factors (Yang et al, ). In a study conducted in the Hetao region in China, it was also shown that capillary levels depend on plant growth stage (from the viewpoint of root development), groundwater depth and soil water content between irrigation events.…”
Section: Resultsmentioning
confidence: 99%